Cheek and Periorbital Peculiar Discoid Lupus Erythematosus: Rare Clinical Presentation Mimicking Tinea Faciei, Cutaneous Granulomatous Disease or Blepharitis - Satoshi Nakamura; Tomoko Yamada; Naoka Umemoto; Toshinobu Nakamura; Koji Wakatabi; Eri Iida; Masumi Masaki; Maki Kakurai; Toshio Demitsu (Karger Publishers, 2015)
We present clinically peculiar facial discoid lupus erythematosus (DLE) that mimicked tinea faciei. Although DLE is a chronic autoimmune dermatosis, it has a variety of rare clinical presentations, including periorbital DLE, comedonic DLE and hypertrophic DLE recently. In this case, a scaly, erythematous lesion on the eyelid and the central healed, mildly elevated, annularly distributed facial DLE mimicked tinea faciei, complicating our diagnosis.